Educational Resources Website for SMK Ulu Tiram - Suhaimi, Nur Syazwani; Sahid, Mohd Zanes (Applied Information Technology And Computer Science, 2025)
In SMK Ulu Tiram, limited exposure to technology in daily secondary school settings necessitates reliance on physical textbooks. However, fluctuating student enrollment poses resource management challenges, with insufficient and deteriorating school-provided textbooks. A survey conducted via Google Form revealed issues in resource storage and management of educational resources. Manual production of modules by school staff results in printing issues, requiring the module to be reproduced. Therefore, they need to provide additional modules. This causes a lot of space, and they don’t have a proper space to store the modules. Teachers face time constraints explaining workflows or solutions, resorting to post-work WhatsApp sessions. Since WhatsApp is typically used for personal purposes, students could find it difficult to retain everything related to their studies during the asynchronous discussion. There’s a need for a mechanism to store and access information beyond the school sessions. To overcome these challenges, a proposed solution involves the development of an Educational Resources Website. This digital platform aims to replace manual processes, mitigating paper-related problems and serving as a centralized repository for free-access materials. By facilitating student interaction and collaboration, the platform seeks to enhance the educational experience at SMK Ulu Tiram, improving resource management for the school. The teachers will also have the ability to share learning materials to their students via online.